Psychiatric Disorders and Obesity in Childhood and Adolescence-A Systematic Review of Cross-Sectional Studies - Ioulia Kokka; Iraklis Mourikis; Flora Bacopoulou (MDPI AG, 2023)
Obesity and psychiatric disorders have high prevalence and are both considered major health problems. Within the last decades, the rates of obesity have risen over 6%, while the prevalence of psychiatric disorders is over 12% for children and adolescents. The aim of this study was to systematically review the evidence regarding the relation of obesity and psychiatric disorders in childhood and adolescence. This review, based on the PRISMA guidelines, included cross-sectional studies published within the last decade, pertaining to the relation between psychiatric disorders and obesity in children and adolescents up to the age of 19 years. Studies on eating disorders were excluded. A total of 14 studies of 23,442 children and adolescents that investigated the relation of obesity with anxiety, mood disorders, and psychosis were included in this systematic review. Nine of the included studies reported a significant relationship between the psychiatric disorder under investigation and obesity. Understanding the nexus between obesity and psychiatric disorders in children and adolescents is of great importance, given the alarming increase in both conditions in youth. Such findings could facilitate the development and implementation of targeted interventions.